Math, asked by geetanshupal965, 4 months ago

The factor of 64a 3 - 27b 3 - 144a 2 b + 108ab 2 *
(I).( 4a + 3b ) 3
(ii).( 4a – b ) 3
(iii).( 4a - 3b ) 3
(iv).( 4a - 3b ) 2​

Answers

Answered by 11169
0

Answer:

Answer :

Concept Used:

(a – b)3 = a3 – b3 – 3a2b + 3ab2

Explanation:

64a3 – 27b3 – 144a2b + 108ab2

= (4a)3 – (3b)3 – 3 (4a)2 (3b) + 3 (4a) (3b)2

= (4a – 3b)3

= (4a – 3b) (4a – 3b) (4a – 3b)

Step-by-step explanation:

Please mark me as brainlist only one brainlist please

Similar questions